Features of serving the sentence of imprisonment convicted juveniles - Романов, М. В. (Theory and practice of jurisprudence, 2016)
The article identified specific institutions, in which are serving sentences of imprisonment juvenile convicted. The basic direction of activity of these institutions is education. Expressed opinion about the basic things that make inefficient activity performance of imprisonment in respect of specified categories of prisoners